GAMBARAN TINGKAT PENGETAHUAN IBU NIFAS TENTANG TANDA BAHAYA POSTPARTUM DI RSIA SITI HAWA PADANG - Arief Rinaldy; Abdullah, Dessy; Revivo Rinda Pratama; Berri Rahmadhoni; Nofrina Putri Melati; Mashdarul Ma'arif (Nusantara Hasana Journal, 2024)
The period of nifas (postpartum) is the recovery time of nine months of pregnancy as well as the birth process. This period of nifas lasts for about 6 weeks. This period occurs physiological and psychological changes, namely: physical changes, uterine involution and lochea expenditure, lactation / maternal milk expenditure, changes in other body systems and psychic changes. The purpose of the study is to find out the picture of the level of knowledge of mothers based on age, education, parity and occupation. The research method is descriptive quantitative with sample techniques i.e. total sampling. The number of samples of this study is 60 samples. The data was taken by way of a live interview with a questionnaire to respondents. Data is processed using SPSS in the form of tables. The results of the study were obtained the most at the age of 20-35 years a total of 52 people (86.7%) and have good knowledge at the age of > 35 years as many as 6 people (85.7%), The most high school education as many as 31 people (51.7%) and have a fairly good knowledge in college as many as 22 people (81.5%), The most parity < 2 children as many as 3 people (100%), as well as the most jobs not working as many as 37 people (61.7%) and have a fairly good knowledge of those who do not work as many as 30 people (81.1%). The results showed that the level of knowledge of mothers is mostly knowledgeable, this is influenced by several factors, namely age, education, parity and occupation factors.